Investigating the potential of Nigella Sativa and thymoquinone in salvaging the embryo from effects of toxic paternal exposure to cyclophosphamide - Abdul Rahman, Suzanah; Abdul Samat, Nadia Hanis; Ahmad, Nur Amalina; Abdullah, 'Afif Raihan; Mohd Zahri, Syazana; Kamarzaman, Saheera (Kulliyyah of Medicine, International Islamic University Malaysia, 2017)
Background: Exposure to cyclophosphamide (CPA) during chemotherapy results in over-production of reactive oxygen species and oxidative stress thus causing sperm defects following disturbance to the genetic material of male germ cells. The goal of this study is to assess the potential effects of Nigella sativa extract (NSE) and thymoquinone (TQ) on sperm and embryo quality subsequent to paternal exposure to a toxic level of CPA. Methods: Thirty-six male ICR mice were divided into six groups; (I) Vehicle-treated control (normal saline), (II) CPA-only, (III) TQ-only, (IV) NSE-only, (V) CPA followed by TQ and (VI) CPA followed by NSE. Treatment with 200mg/kg CPA and 10mg/kg of both NSE and TQ were given by intraperitoneal injection. Animals were sacrificed at day 33 by cervical dislocation and sperm from caudal epidydymis were taken for analysis and in vitro fertilisation (IVF) with eggs from untreated female. Fertilization rates and embryo development were monitored for 5 days. Results: TQ and NSE supplementation to CPA-exposed male mice have no significant effect on the total number of sperm when compared to CPA-only exposed mice. NSE and TQ supplementation have been shown to have significant effects on the percentage of motile sperm as well as the number of abnormal sperm. Four types of sperm abnormalities were observed and they included folded sperm, amorphous, banana-like and the head lacking of the usual hook. The embryo quality showed a significant improvement by the supplementation of TQ and NSE to CPA-exposed male mice. Conclusion: Both NSE and TQ exhibited chemopreventive potential against the toxic alkylating effects of CPA on the reproductive capacity and fertility of mice.